APLIKASI MOBILE PORTAL BERITA GANTO.OR.ID BERBASIS ANDROID - Afrinaldi Afrinaldi; Asrul Huda; Denny Kurniadi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2015)
The development of mobile communication technology leads people to use technology not only as a communication tool, but also as a tool to find a variety of information, and news. Today's society considers mobile communications media as a very practical needs in its use and has high mobility. Many news portal now also includes news portal applications for mobile devices. Ganto UNP news portal does not provide the application which led to the news portal infrequently accessed through mobile devices because of the view that is not user-friendly when accessed through the device. To overcome this problem, it is necessary to design a mobile application for Ganto news portal. So that mobile device users no longer need to access the Ganto news portal through a web browser. Simply by using the mobile application. This application was designed with the Java programming language, Eclipse as an IDE, Eclipse ADT as a plugin on android, and the Android SDK for Android application development, as well as the AVD emulator to run the android system. Programming language used to build web-service is PHP programming language and MySQL DBMS that has owned news portals Ganto as data storage server. By utilizing the Android mobile device technology, successfully obtained an application that can accommodate the needs of people who have a high level of mobility to access information on Ganto news portals anytime and anywhere effectively and efficiently.  Keywords   : News Portal, Ganto, Android, web-service.